“NAD‐display”: Ultrahigh‐Throughput in Vitro Screening of NAD(H) Dehydrogenases Using Bead Display and Flow Cytometry - Lindenburg, Laurens; Hollfelder, Florian (Angewandte Chemie International Edition, 2021)
NAD(H)‐utiliing enzymes have been the subject of directed evolution campaigns to improve their function. To enable access to a larger swath of sequence space, we demonstrate the utility of a cell‐free, ultrahigh‐throughput directed evolution platform for dehydrogenases. Microbeads (1.5 million per sample) carrying both variant DNA and an immobilised analogue of NAD+ were compartmentalised in water‐in‐oil emulsion droplets, together with cell‐free expression mixture and enzyme substrate, resulting in the recording of the phenotype on each bead. The beads’ phenotype could be read out and sorted for on a flow cytometer by using a highly sensitive fluorescent protein‐based sensor of the NAD+:NADH ratio. Integration of this “NAD‐display” approach with our previously described Split & Mix (SpliMLiB) method for generating large site‐saturation libraries allowed straightforward screening of fully balanced site saturation libraries of formate dehydrogenase, with diversities of 2×104. Based on modular design principles of synthetic biology NAD‐display offers access to sophisticated in vitro selections, avoiding complex technology platforms. A detection system was devised to screen dehydrogenase enzymes (DH) at ultrahigh‐throughput in in vitro droplet compartments. An NAD(H) analogue and a DH DNA library were co‐immobilised on beads. Water‐in‐oil emulsion droplets containing cell‐free expression mix and substrate allow compartmentalised protein production and catalysis. A fluorescent sensor of NAD(H) redox state was loaded onto beads, allowing bulk sorting of 2×104 DH variants in a day by flow cytometry.